Role of social media in Political Awareness and Political Participation an Empirical Study of Dibrugarh District (International Journal of Food and Nutritional Sciences, 2022)
How we talk to one another and engage with others has been revolutionised by social media. It has also altered people's participation in political life. The advent of social media has drastically altered human interaction. The way voters participate in elections has also been affected. The consequences of the results with special reference to Dibrugarh District has been discussed, and directions for further study are suggested. These findings demonstrate the powerful influence that social media platforms have on individuals' ability to keep up with current political events and take part in them. In comparison to individuals who don't use social media, those who do tend to be more politically engaged and knowledgeable. According to the research, social media may be a useful platform for political mobilisation and can encourage individuals to engage in political discourse and debate. on individuals' ability to keep up with current political events and take part in them. In comparison to individuals who don't use social media, those who do tend to be more politically engaged and knowledgeable.